Unveiling the Transformational Impact of Digital Technologies on Accounting and Finance - Fazrian Thursina (Westscience Press, 2023)
Digital technologies have significantly transformed the fields of accounting and finance, revolutionizing traditional practices and shaping new avenues for research and professional development. This research conducts a comprehensive bibliometric analysis to uncover the transformative impact of digital technologies on accounting and finance. Using bibliometric techniques, key trends, influential authors, and notable publications in this domain were identified. The analysis explores the interdisciplinary nature of digital technologies in accounting and finance, highlighting the integration of technologies with subfields such as financial reporting, auditing, and financial management. The findings provide valuable insights into the evolving landscape of accounting and finance in the digital age, assisting practitioners, policymakers, and researchers in understanding and harnessing the potential of digital technologies.